MENTALITY, ETHNIC CHARACTER, IDENTITY AND SPIRITUAL SELF-EXERCISE OF A PERCEPTIONAL UKRAINIAN AS A FACTOR OF THE PURPOSE OF UKRAINE - Kolisnik, Alexey Petrovich (Psychological Prospects Journal, 2013)
The experience of interacting with the world of a particular community is preserved in its culture, which has material and spiritual aspects. The spiritual side of culture is transmitted through its reference carriers from generation to generation. A large part of the culture of the reference community is developed by the human individual in the course of socialization, acculturation and personalization, involuntarily through identification with reference individuals and reference groups. The reference culture is presented in the psyche of the human individual in the form of mentality as a cultural unconscious, which he is not really aware of and is not really controlled.